“QUEM TEM MEDO DA PALAVRA NEGRO? ”: MORENOS, MISTURADOS, MESTIÇOS, CAFUSOS, MULATOS, ESCUROS, PRETO SOCIAL PARTICIPANTES DO CLUBE 13 DE MAIO – PONTA GROSSA (PR) - Santos, Merylin Ricieli dos (2016)
The research presents a study of speeches built around the black Club, located in Ponta Grossa (PR). It deals with the construction of the identities of the individuals who participate or have participated, from the evidential paradigm, Carlo Ginzburg (1990). The work aims to seek what spaces, negotiations, interdictions, silences, visions; meanings attributed to the Club by the local society as well as understand how the regulars and non-regulars see the Club. It yearns still answer, which the Club's relationship signs with society and society with the Club. It seeks to highlight a marginalized space while a black club contributed to various local identity buildings. The Club May 13 is a Recreational Society, founded by free blacks in the post-abolition period, founded in 1890 in the city of Ponta Grossa, and that at the time of its creation had a very suggestive nomenclature: Literary Club and Recreative May 13. The corpus of the research consists of a set of black people speeches built between the months of January and February 2016 in the form of oral interviews regarding this recreational society. The research is qualitative (MINAYO, 1994) and part of the analysis of materials are the result of oral interviews (MINAYO, 2001), the other part corresponds to the status of the Club, the Sentence Report and Overturning Process the entity in question. By analyzing the two documents it seeks to highlight the issue of the club's relationship with the city, since they are taken as discourses on May Thirteen Club and its social dynamics. From the analysis of interviews, it presents the signs involving racial designation of the regulars of the club, as well as discussions on how these people saw themselves in this black sociability, they saw the club in the society in which it was entered, as well as their perceptions of race relations intertwined in this. The theoretical and methodological reference analysis depart from the proposal of the Bakhtin Circle (1929/2005) about the dialogic and responsive communication in conjunction with the methodology guided the evidential paradigm, Ginzburg (1990). To the question of black identity, the reference was Munanga (2012), Hall (2002, 2006), Gomes (2005), Souza (1983) and on this category Munanga (2010) believes that to build a collective black identity it is needed a process of deconstruction and authenticity, not related to a negative black history rooted in colonial historiography. The research deals with the relationship between literacy and black organizations, discussion that comes from the club's name as a literary in its foundation. It brings a discussion about the history of black Club here questioned, whose function is to contextualize the study object and discuss its relationship to Eurocentric society that was inserted. The final considerations, through questioning and analysis of the statements and documents about the Club, indicate that the main results point to the act of creating a black club in Ponta Grossa as a form of resistance. The interdictions assigned to the club suggest the no place of it in the city. Although the club appears as a invisible and negated space by its non goers, the processes of identity constructions occurred inside pervade the negative borders and enter blacks as subjects of various social practices, positiving their experiences and enhancing their socio-cultural experiences.